2020
DOI: 10.3389/fpls.2020.566824
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exogenous Putrescine on Delaying Senescence of Cut Foliage of Nephrolepis cordifolia

Abstract: Senescence is the main limitation for cut foliage display in vase. Naturally occurring polyamines such as putrescine (Put) have been considered effective anti-senescence agents. However, effect of Put on cut foliage in vase in a realistic indoor environment has not yet been revealed. In the present study, effects of Put spraying on the postharvest performance of cut foliage of Nephrolepis cordifolia L. were investigated. Cut fronds sprayed with deionized water (Put0) showed visible injuries after 10 days in va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Exogenous Put significantly increased soluble sugar accumulation under drought stress, which is closely related to a signaling adjustment to environmental response. It is likely because Put is polycationic, meaning it can bind and stabilize osmotic micromolecules ( Qu et al, 2020 ). Sucrose metabolism is often used as an indicator of environmental stress and plant adaptability.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous Put significantly increased soluble sugar accumulation under drought stress, which is closely related to a signaling adjustment to environmental response. It is likely because Put is polycationic, meaning it can bind and stabilize osmotic micromolecules ( Qu et al, 2020 ). Sucrose metabolism is often used as an indicator of environmental stress and plant adaptability.…”
Section: Discussionmentioning
confidence: 99%
“…They are involved in various physiological processes, such as cell division, differentiation, and stress response. Recent studies have shown that treating cut flowers with polyamines, such as putrescine and spermidine, can improve their vase life by reducing senescence and preserving flower quality (Qu et al, 2020;Mazrou et al, 2022). Chitosan is a biodegradable polymer derived from chitin, which is found in the shells of crustaceans.…”
Section: Smart Greenhouse Technologymentioning
confidence: 99%
“…Polyamines, putrescine (Put), spermidine (Spd) and spermine (Spm), are widely present in plants and are closely related to plant growth and development. Qu et al found that exogenous Put significantly ameliorated the losses of Chl and improved photochemical capability and prevented membrane impairment of Nephrolepis cordifolia [ 208 ]. Tavallali et al reported exogenous Spd significantly increased levels of phenolic and flavonoid compounds in pot marigold [ 209 ].…”
Section: The Mechanism By Which Exogenous Substances Regulate Ros Met...mentioning
confidence: 99%